2020
DOI: 10.1002/fsn3.1932
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, texture, and probiotic survivability of oat‐based yogurt using aquafaba as a gelling agent

Abstract: Fermented dairy products contain essential nutrients and bioactive ingredients beneficial for human health, and therefore, their moderate consumption is recommended for the general population as part of a healthy eating regime (Wong et al., 2020). On the other hand, dairy products are responsible for several diet-related adverse effects such as lactose intolerance and dairy protein allergy and thus may not be tolerated by an increasing segment of the population (Gupta et al., 2010). In addition, animal welfare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…As for the fat content, in some studies, it was not detected or was below the detection limit [ 4 , 22 ]. However, in our study, fat content was detected and was 0.14 ± 0.01, which is in accordance with [ 23 ], who reported a value of 0.13 ± 0.03 and with [ 21 ], who reported a value of <0.1%. A study on boiled chickpeas [ 24 ] reported a significant loss of small fractions of fats upon boiling.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As for the fat content, in some studies, it was not detected or was below the detection limit [ 4 , 22 ]. However, in our study, fat content was detected and was 0.14 ± 0.01, which is in accordance with [ 23 ], who reported a value of 0.13 ± 0.03 and with [ 21 ], who reported a value of <0.1%. A study on boiled chickpeas [ 24 ] reported a significant loss of small fractions of fats upon boiling.…”
Section: Resultssupporting
confidence: 92%
“…As for the ash content, the determined value in this study was 0.49% ± 0.01, which agrees with the previously reported values in the literature, which were 0.4%, 0.5%, and 0.6% in [ 4 , 21 , 22 ], respectively. The fiber content of CA was reported in very few studies and was 0.69 ± 0.03 and 4.04 ± 0.09 in [ 21 , 23 ], respectively. In this study, the determined value was 0.51 ± 0.16.…”
Section: Resultsmentioning
confidence: 99%
“…104 In another study, an oat-based yogurt was also developed using oat milk and probiotics (Streptococcus thermophilus and Lactobacillus bulgaricus) with fructose (AF) and vegetable oil (VO). 105 The yoghurt fermented by oat milk compared well with yoghurt fermented by cow milk in terms of the nutrient composition and sensory evalu-Fig. 3 Potential applications of oat milk in the substitute milk industry.…”
Section: Fermented Oat Milk Products and Beveragesmentioning
confidence: 99%
“…Plant-based yoghurts produce weaker gels than their dairy counterparts and are highly prone to syneresis, regardless of the type of raw material used [ 36 , 57 , 153 , 156 ]. While the discussed processing strategies ( Section 3 ) are helpful, researchers have been developing fermentation protocols which can simultaneously achieve optimal flavour and texture in the final yoghurt analogue.…”
Section: Fermentation As a Strategy To Improve Organoleptic Propertie...mentioning
confidence: 99%